Applications of Polyaniline-Based Molybdenum Disulfide Nanoparticles against Brain-Eating Amoebae - Sumayah, Abdelnasir; Mungroo, Mohammad Ridwane; Chew, Jactty *; Siddiqui, Ruqaiyyah; Khan, Naveed Ahmed; Ahmad, Irfan; Shahabuddin, Syed; Ayaz, Anwar * (American Chemical Society, 2023)
Primary amoebic meningoencephalitis and granulomatous amoebic encephalitis are distressing infections of the central nervous system caused by brain-eating amoebae, namely, Naegleria fowleri and Acanthamoeba spp., respectively, and present mortality rates of over 90%. No single drug has been approved for use against these infections, and current therapy is met with an array of obstacles including high toxicity and limited specificity. Thus, the development of alternative effective chemotherapeutic agents for the management of infections due to brain-eating amoebae is a crucial requirement to avert future mortalities. In this paper, we synthesized a conducting polymer-based nanocomposite entailing polyaniline (PANI) and molybdenum disulfide (MoS2) and explored its anti-trophozoite and anti-cyst potentials against Acanthamoeba castellanii and Naegleria fowleri. The intracellular generation of reactive oxygen species (ROS) and ultrastructural appearances of amoeba were also evaluated with treatment. Throughout, treatment with the 1:2 and 1:5 ratios of PANI/MoS2 at 100 μg/mL demonstrated significant anti-amoebic effects toward A. castellanii as well as N. fowleri, appraised to be ROS mediated and effectuate physical alterations to amoeba morphology. Further, cytocompatibility toward human keratinocyte skin cells (HaCaT) and primary human corneal epithelial cells (pHCEC) was noted. For the first time, polymer-based nanocomposites such as PANI/MoS2 are reported in this study as appealing options in the drug discovery for brain-eating amoebae infections.